1993
DOI: 10.1093/cvr/27.8.1462
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of myocardial oedema by magnetic resonance imaging early after coronary artery occlusion with or without reperfusion

Abstract: Magnetic resonance imaging allows evaluation of myocardial oedema associated with acute coronary occlusion and reperfusion, and analysis of its spatial distribution. Changes in myocardial water content occurring early during acute myocardial infarction allow quantification of the area at risk and detection of reperfusion by magnetic resonance imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
136
1
6

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(155 citation statements)
references
References 0 publications
12
136
1
6
Order By: Relevance
“…Advances in MR such as novel contrast agents [27], T2 weighted sequences for the detection of oedematous tissue [28] or quantitative assessment of myocardial perfusion were initially validated in pigs [29]. Schmitt et al demonstrated correlation between experimentally reduced coronary perfusion measured with quantitative CMR and fluorescently labelled microspheres [30].…”
Section: Discussionmentioning
confidence: 99%
“…Advances in MR such as novel contrast agents [27], T2 weighted sequences for the detection of oedematous tissue [28] or quantitative assessment of myocardial perfusion were initially validated in pigs [29]. Schmitt et al demonstrated correlation between experimentally reduced coronary perfusion measured with quantitative CMR and fluorescently labelled microspheres [30].…”
Section: Discussionmentioning
confidence: 99%
“…16 Using T2-weighted cardiac magnetic resonance (CMR), it is possible to visualize edema in the myocardium retrospectively, even several days after coronary occlusion. 17,18 Experimental studies have demonstrated that the extent of edema is comparable to histopathological and fluorescein measurements of the area at risk. 19 Furthermore, the quantification of irreversible myocardial injury using delayed contrast-enhanced CMR has been extensively validated in acute and chronic settings.…”
Section: How To Measure the Extent Of Myocardium At Riskmentioning
confidence: 94%
“…Therefore, an interesting application of T2W imaging has been in the demarcation of the area at risk associated with acute MI. 15,16 The area at risk during an acute coronary event is the salvageable myocardium (hypoperfused but noninfarcted), the salvation of which can determine the therapeutic efficacy of reperfusion therapy. 17 The clinical significance of detecting the area at risk cannot be overemphasized.…”
Section: T2 Mappingmentioning
confidence: 99%